2003
DOI: 10.1086/344722
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Line Opacity of MgH in Cool Stellar Atmospheres

Abstract: A new, complete, theoretical rotational and vibrational line list for the A-X electronic transition in MgH is presented. The list includes transition energies and oscillator strengths for all possible allowed transitions and was computed using the best available theoretical potential energies and dipole transition moment function with the former adjusted to account for experimental data. The A-X line list, as well as new line lists for the B'-X and the X-X (pure rovibrational) transitions, were included in com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…In the case of the Q 1 and Q 2 lines of MgH, this leads to f v j ,v j = f v v /2 at the large j limit, whereas the similar formulae (3) and (4) of Weck et al (2003) …”
Section: Recalculation Of the Hönl-london Factorsmentioning
confidence: 92%
See 1 more Smart Citation
“…In the case of the Q 1 and Q 2 lines of MgH, this leads to f v j ,v j = f v v /2 at the large j limit, whereas the similar formulae (3) and (4) of Weck et al (2003) …”
Section: Recalculation Of the Hönl-london Factorsmentioning
confidence: 92%
“…As different values can be found in the literature for the oscillator strengths of the lines under interest (Kurucz's values are reported in Table 1; Weck et al 2003, derive twice smaller values), we have found necessary to recalculate the Hönl-London factors of these lines. This calculation is based on the most recent basic reference works in this field by Larsson (1983) and Whiting & Nicholls (1974).…”
Section: Recalculation Of the Hönl-london Factorsmentioning
confidence: 97%
“…Convective energy transport and velocities are calculated using mixing length theory with a mixing length of 2.0 pressure scale heights, and overshoot is treated as an exponential velocity field with a scale height based on the RHD simulations of Ludwig et al (2002Ludwig et al ( , 2006 and Freytag et al (2010Freytag et al ( , 2012; an additional advective mixing term due to gravity waves is included as described in Freytag et al (2010). All relevant molecular absorbers are treated with line-by-line opacities in direct opacity sampling as in Allard et al (2003b); regarding this, the molecular line lists have been updated as follows: watervapor (BT2, Barber et al 2006), CIA of H 2 (Borysow 2002), and FeH (Plez 1998;Weck et al 2003;Dulick et al 2003). Nonequilibrium chemistry for CO, CH 4 , CO 2 , N 2 , and NH 3 is treated with height-dependent diffusion also based on the RHD simulation results of Freytag et al (2010).…”
Section: Spectral Synthesismentioning
confidence: 99%
“…Both have very similar properties. This is followed by x 2.3, where we discuss the metal hydrides TiH ( Burrows et al 2005), CrH ( Burrows et al 2002), FeH (Dulick et al 2003), MgH (Skory et al 2003;Weck et al 2003a), and CaH (Leininger & Jeung 1995;Weck et al 2003b), which all have similar properties.…”
Section: Introductionmentioning
confidence: 99%